A Spontaneous H2-Aa Point Mutation Impairs MHC II Synthesis and CD4+ T-Cell Development in Mice - Zhao, Yun; Xiong, Juan; Chen, Hai-Xia; Zhang, Min; Zhou, Li-Na; Wu, Yin-Fang; Li, Wei-Jie; Fei, Xia; Li, Fei; Zhu, Chen; Li, Wen; Ying, Song-Min; et al. (Frontiers in Immunology, 2022)
Major histocompatibility complex class II (MHC II) is an essential immune regulatory molecule that plays an important role in antigen presentation and T cell development. Abnormal MHC II expression can lead to immunodeficiency, clinically termed as type II bare lymphocyte syndrome (BLS), which is usually resulted from mutations in the MHC II transactivator (CIITA) and other coactivators. Here, we present a new paradigm for MHC II deficiency in mice that involves a spontaneous point mutation on H2-Aa. A significantly reduced population of CD4+ T cells was observed in mice obtained from the long-term homozygous breeding of lc3b knockout mice; this phenotype was not attributed to the original knocked-out gene. MHC II expression was generally reduced, together with a marked deficiency of H2-Aa in the immune cells of these mice. Using cDNA and DNA sequencing, a spontaneous H2-Aa point mutation that led to false pre-mRNA splicing, deletion of eight bases in the mRNA, and protein frameshift was identified in these mice. These findings led to the discovery of a new type of spontaneous MHC II deficiency and provided a new paradigm to explain type II BLS in mice.